An analysis of cognitive dimensions in reading assessment tasks of the English for Nusantara grade 8 textbook - Chindy Yolanda; Ira Maisarah (Universitas Sanata Dharma, 2026)
Reading assessment plays a crucial role in English language teaching, as it helps measure students’ comprehension and supports the development of thinking skills. In Indonesia, the Merdeka Curriculum emphasizes learner autonomy and high-order thinking skills (HOTS), requiring textbooks to provide assessment tasks that go beyond factual recall. This study aims to examine the cognitive dimensions of reading assessment tasks in the English for Nusantara Grade 8 textbook. Using a descriptive quantitative design, this study analyzed reading assessment through content analysis based on Revised Bloom’s Taxonomy. The reading questions were coded and categorized into one of six cognitive dimensions, and categorized as LOTS or HOTS. The findings reveal that lower-order thinking skills (LOTS) dominate the reading assessment tasks, with remembering (56.0%) and understanding (21.33%) being the most frequent, rather than HOTS questions. It implied that the reading assessment task in the English for Nusantara Grade 8 Textbook may not fully support the development of HOTS that promote students’ critical and analytical reading abilities. These findings suggest that while the textbook partially aligns with the Merdeka Curriculum, greater emphasis on HOTS-based reading assessment is needed to better support students’ critical thinking and the development of reading comprehension.